Laws of domestication and domesticating the law in Yakutian human- animal relations - Ivanova, Aytalina; Stammler, Florian (Routledge, 2025)
Any contemporary practice of humans with animals is regulated by authorities. Within the Arctic, the Republic of Sakha (Yakutia) has been particularly active in legally protecting breeds of animals that the authorities have decided to be important in the area. Laws on reindeer herding, horse herding, and native cattle establish the area as an exceptional place of multi-species pastoralism in the Arctic. In this chapter we analyze the laws according to their orientation toward economic, social-cultural, and genetic significance of the respective animals. Significance, however, is defined by human interests. Legal anthropological analysis shows to what extent specific laws for specific breeds of animals influence livelihoods and cultures of people. We argue for a closer investigation of the overlap between regulations on paper and realities created by lived human-animal experience. In doing so, this chapter draws parallels between people’s efforts in enacting the domestication in their human-animal relations, as well as in their relations to the law. Thus, laws become meaningful for human-animal livelihoods through domesticating them locally: in a mutual process laws are made that fit within the local pastoral livelihood, as well as pastoral practices being adjusted to benefit from laws.